This Penerapan Konseling Kelompok Dengan Teknik Penguatan Positif Untuk Mengentaskan Perilaku Bullying Siswa SMA - Anggareni Ni Luh Trisna; Dartiningsih Made Wery (Jurnal Bimbingan dan Konseling Indonesia, 2023)
This research includes Classroom Action Research (PTK). Action research is "action research conducted by a teacher in a classroom or school, with a focus on improving or strengthening learning processes and practices" The data analysis technique used in this research is quantitative analysis technique, namely analyzing the data obtained through the depiction of numbers to obtain conclusions based on the analysis carried out, it can be concluded that the provision of group counseling with positive reinforcement techniques is very effective to use so as to obtain a decrease in the first action cycle of bullying behavior in students ranging from in cycle I there was a decrease in bullying behavior in students between 28, 23% to 22.22% with an average value as a group of decreasing bullying behavior in students between 25.358% in cycle II to a decrease in bullying behavior in students between 35.38% to 30% with an average value as a group of decreasing bullying behavior of 33.928% so that it can be concluded that the use of group counseling is able to suppress bullying behavior in students in class XI IPS 2 at SMA Negeri 1 Susut in 2023, this means that the behavior of the perpetrator who needs to receive ongoing treatment in accordance with the characteristics of the child's problems so that it is hoped that this child will no longer commit violence both physically and psychologically against his classmates.